Impact of Adjuvant Chemotherapy on Nutritional Status and Functional Capacity in Postoperative Stage III Colorectal Cancer Patients - Dhanny Akbar, Mohammad; Mahendra, Vito; Setiawan, Eko (CV. Dyoqu Publishing Management, 2025)
Background: Colorectal cancer is one of the cancers with high prevalence in Indonesia. Management generally involves surgery and adjuvant chemotherapy. However, chemotherapy often causes side effects that can affect the nutritional status and functional capacity of patients. Nutritional status and Karnofsky index are important indicators in assessing the quality of life of post-chemotherapy patients. Aims: This study aims to analyze the relationship between adjuvant chemotherapy with nutritional status and Karnofsky index in patients with stage III colorectal cancer after surgery. Methods: This study used an analytic observational approach with a cross-sectional design. A total of 65 stage III colorectal cancer patients at Sultan Agung Islamic Hospital Semarang who met the inclusion and exclusion criteria were analyzed using medical record data. Nutritional status was assessed through body mass index (BMI), and Karnofsky index was classified into good and bad categories. Data analysis was performed using the Chi-Square test. Results: Most patients had BMI in the normal category (58.5%) and Karnofsky index in the good category (64.6%). Statistical test results showed that there was no significant relationship between adjuvant chemotherapy and nutritional status (p = 0.356) or Karnofsky index (p = 0.841). Conclusion: Adjuvant chemotherapy was not significantly associated with nutritional status and Karnofsky index in post-surgical stage III colorectal cancer patients. This study emphasizes the importance of a holistic care approach and nutritional support in maintaining patients' quality of life.